Cell–Cell Interaction Proteins (Gap Junctions, Tight Junctions, and Desmosomes) and Water Transporter Aquaporin 4 in Meningothelial Cells of the Human Optic Nerve - Zeleny, Thi Ngoc Co; Kohler, Corina; Neutzner, Albert; Killer, Hanspeter E.; Meyer, Peter (Frontiers in Neurology, 2017)
Purpose: Meningothelial cells (MECs) play a central role in the maintenance of cerebrospinal fluid (CSF) homeostasis and in physiological and pathophysiological processes within the subarachnoid space (SAS) linking them to optic nerve pathologies. Still, not much is known about their structural properties that might enable MECs to perform specific functions within the optic nerve microenvironment. Methods: For closer characterization of the structural properties of the human meningothelial cell layer in the arachnoid we performed immunohistological analyses to evaluate the presence of cell-cell interaction markers, namely markers for tight junctions (JAM1, occluding, claudin 5), gap junctions (connexin 26 and 43) and desmosomes (desmoplakin) as well as for water channel marker aquaporin 4 (AQP4) in retrobulbar, mid-orbital and intracanalicular human optic nerve sections. Results: MECs displayed immunopositivity for markers of tight junctions (JAM1, occluding, claudin 5) and gap junctions (connexin 26 and 43) as well as for aquaporin 4 water channels. However no immunopositivity was found for desmoplakin. Conclusion: MECs are connected via tight junctions and gap junctions and they possess AQP4 water channels. The presence of these proteins emphasizes the important function of MECs within the optic nerve microenvironment as part of the meningeal barrier. Beyond this barrier function, the expression of these proteins by MECs supports a broader role of these cells in signal transduction and CSF clearance pathways within the optic nerve microenvironment.